Association of Insulin Resistance With Cardiovascular Risk Factors and Sleep Complaints: A 10-Year Follow-Up - Podlipskyte, Aurelija; Kazukauskiene, Nijole; Varoneckas, Giedrius; Mickuviene, Narseta (Frontiers in Public Health, 2022)
The aim of the study was to investigate the association of insulin resistance (IR) with cardiovascular risk factors and sleep complaints among citizens of Palanga over a 10-year follow-up period. This epidemiological longitudinal cohort study was performed with 835 subjects. Methods All participants were evaluated for sociodemographic, clinical and cardiovascular risk factors, behavioral factors, self-perceived health and biochemical analysis. IR was evaluated using the homeostasis model assessment of IR (HOMA-IR). Results All study participants were stratified into two groups, without IR (HOMA-IR ≤ 2.7) and with IR (HOMA-IR > 2.7). The analysis of parameters between the two study groups showed statistically significant relationships between IR, cardiovascular risk factors and sleep complaints within the 10-year period. After adjusting for a 10-year period, sex, age, body mass index, physical activity, education, systolic and diastolic blood pressures, presence of disease, total cholesterol, triglyceride levels, metabolic syndrome (MetS) and diabetes mellitus (DM), IR was statistically significantly more frequent in subjects with increased sleep latency [odds ratio (OR) 1.37, 95% CI 1.01–1.93; p = 0.043], snoring frequency (OR 1.37, 95% CI 1.05–1.79; p = 0.020) and very loud snoring (OR 1.34, 95% CI 1.04–1.74, p = 0.026). Conclusions The incidence of obesity, MetS, DM, elevated fasting glucose level, triglyceridemia and sleep complaints became more frequent after a 10-year period in subjects with IR. Over a 10-year period, IR was significantly associated with an increase in sleep complaints: sleep latency reflecting difficulty to fall asleep, snoring and very loud snoring.